Effectiveness of RTLH Development in Madiun District - Wuryani, Siti (Decision, 2022)
The house (place to live) is one aspect of social welfare that must be fulfilled. Because the house is the main need for human life apart from clothing and food, where humans can shelter, maintain and also improve the quality of their life. The house not only has strategic value for the lives of its residents. This strategic value is reflected in the position of the house as a center of activity in carrying out its functions, especially the function of educating children and developing family members. Based on this, every family always strives to have a house that is livable, even though objectively not all families can afford it. make his wishes come true. This is caused by various factors, especially family economic factors due to poverty. Recipients of RTLH rehabilitation assistance are MBR/or poor people who meet the following requirements: Indonesian citizens who are married. Own or control land based on legal rights, not disputed land and in accordance with regional spatial planning Do not yet own a house or own and occupy the only house in an uninhabitable condition 4.Have never received RTLH rehabilitation assistance or government assistance for housing programs Earn the maximum income equal to the UMR of Madiun Regency Willing to be self-sufficient. Aid recipients who have been registered in the DTKS are the Integrated Social Welfare Data and/or Madiun Regency RTLH Data base for 2015 and or the village head's proposal which is then forwarded to the Madiun Regency Housing and Settlement Area Service.The implementation of the RTLH development program from 2018 to 2021 has been running effectively, this can be seen from the accuracy of the targets where those who receive this assistance are communities who have the RTLH requirements and are registered in the 2015 PBDT, with 9,010 RTLH being eradicated. And it is hoped that it will be implemented in 2015. 2022 can also be completed according to the specified time.